Hybrid vehicle brushless double-stator electric machine - YANG YUN; XU QIWEI; ZHAO MENG; LUO XIAOXIAO; SUN JING; YE XIAOYUN; CHEN JINLUO; JIANG XIAOBIAO (2017)
The invention discloses a hybrid vehicle brushless double-stator electric machine which includes an electric machine casing (5). A first stator (1), a magnetic adjusting ring (3) and a second stator (4) are arranged in order from left to right inside the electric machine casing (5). An internal rotor (2) is disposed inside the first stator (1). The internal rotor (2) is connected to an output shat (6) of an internal combustion engine. The output shaft (6) of the internal combustion engine is supported in a left side bearing hole of the electric machine casing (5). The magnetic adjusting ring (3) is connected to a primary decelerator input shaft (3-3) which is supported in a right side bearing hole of the electric machine casing (5). The shaft axes of the first stator (1), the internal rotor (2), and the magnetic adjusting ring (3) are overlapped with the shaft axis of the second stator (4). The electric machine herein has no brush or slip ring structures, can reduce structural complexity of electric machines,